Um Modelo Computacional para magneto-acreção e ventos magneto-centrífugos em Estrelas T Tauri clássicas - Gustavo Henrique Reis de Araujo Lima (2010)
Classical T Tauri stars are young low-mass stars (=2M.), with spectral types between F and M, that are still accreting material from a circumstellar disk. Spectral observations of this type of stars reveal a wide range of line profiles, many of which show signs of matter inflow and outflow. The Ha line is the most commonly observed line profile in these stars due to its intensity and its strong dependence on the characteristics of the surrounding environment of these objects. In this work, we have developed a model that uses a dipolar axisymmetric stellar magnetic field to model the stellar magnetosphere, and a modified Blandford & Payne model in our disk wind region. The star is divided in two regions: the stellar photosphere, and the accretion shockregion, both emitting as blackbodies with different temperatures. The accretion disk is opaque and its contribution to the radiation field is neglected due to its low temperature. The Hydrogen level populations are calculated using a three-level atom with continuum. We use the Sobolevresonant co-moving surfaces approximation to calculate the radiation field characteristics inside the studied region, and a ray-by-ray method to calculate the resulting Ha line profile. This is only the second model that takes into consideration a magnetosphere radiatively coupled with a disk wind component to calculate line profiles in classical T Tauri stars. However, this is the first model that uses a consistent magneto-centrifugally accelerated disk wind that does not violatethe Blandford & Payne launching condition. We have calculated Ha line profiles using the standard stellar parameters for a classical T Tauri star, changing the various characteristic parameters used to define the magnetosphere and the disk wind in our model. Analysing the various calculated line profiles, we were able to infer the most important parameters that influence the Ha line profile. In all cases, we have used amass loss rate (Mperda) to mass accretion rate (Macr) ratio of 0.1. We have calculated profiles showing how the. Macr coupled with the .Mperda, and with different magnetosphere and disk wind temperatures affect the Ha line. We have also investigated which regions inside the disk windare the most important for the formation of the Ha line, and, then, how the disk wind size affects this line. Changing the parameters used to define our self-similar disk wind solution (angular momentum, mass flux to magnetic flux ratio and launching angle), we were able to infer theireffects on the Ha line profiles. And, finally, we have investigated the effects of the system inclination on the Ha line. Our results show that the Ha line is strongly dependent on the densities and temperatures inside the magnetosphere and the disk wind region. They show that the bulk of the Ha flux comes, in most cases, from the magnetospheric component for standard classical T Tauri star parameters, but the disk wind contribution becomes more important as the mass accretion rate, thetemperatures and densities inside the disk wind increase, and can even surpass the magnetospheric contribution in the most extreme scenarios. The results also show that for very low mass accretion rates (Macr < 10-9M. yr-1), the effects of the disk wind contribution to the Ha line canbe neglected. We have found that the blue-shifted absorption feature in the Halfa line disappears if the disk wind temperature is below a certain transition value, which depends on the mass loss rate. This blue-shifted absorption feature is very dependent on the size of the disk wind, and itsposition on the line profile is defined, mostly, by the disk wind parameters that characterize its angular momentum, mass to magnetic flux ratio and launching angle. We have also found that most of the disk wind contribution to the Ha line is emitted at the innermost region of the diskwind. We have been able, so far, to reproduce Ha lines that resemble most of the large variety of observed line profiles for classical T Tauri stars. However, we have spectra of objects with very different characteristics, and we plan to use this model to calculate line profiles for these objects and then compare with the observations. This model may also be useful to better understand the Herbig Ae/Be stars environment